ORGANIC AGRICULTURE IN REPUBLIC OF MACEDONIA AND POSSIBILITIES FOR ENHANCING - Hadzi Naumova-Mihajlovska, Katerina (Integrated Business Faculty, Skopje, 2017)
Main characteristic of Macedonian agriculture is traditional extensive agriculture present in mountain areas, which is main precondition for the development of organic production. In recent years, the Republic of Macedonia notes increased inters for organic agriculture; in the organization of the organic sector are included: producers, cooperatives, associations, counseling stakeholders, control and certification bodies and government institutions. Practice shows that there is a lack of organization and coordination among them, which results with unstable sale of organic production. The attempt of the paper is to explore and analyze the organic agriculture production in the Republic of Macedonia in order to show some perspective trends for further enhancing and development of organization in the form of policy or strategy for quality work and organization of organic sector.
Keywords: organic agriculture, organic production, farmer organization, Republic of Macedonia JEL